PRINSIP PEMERINTAHAN DALAM ISLAM MENURUT MUHAMMAD ASAD - Amir, Ahmad Nabil (Jurnal Suara Politik, 2024)
The paper discusses Muhammad Asad’s work on the principle of Islamic governance and its basic constitution and foundational structure. In this regards, he formulated the constitutional ideas of Islamic state whose constitution contains the provision of Islamic law that practiced and implement the norms stated in the Qur’an and hadith. This ideas was partly enshrined in the Pakistan constitutional law whose political establishment was formed in 1947. It essentially discussed Muhammad Asad’s political ideas and its underlying philosophy as espoused in his works, such as The principles of state and government in Islam, This law of ours and other essays, Islamic constitution making, journal Arafat, The message of the Qur’an, Sahih al-Bukhari the early years of Islam and,  etc. The study is based on qualitative methods in the form of library research. The data were analysed using descriptive, analytical and comparative methods. The finding shows that Muhammad Asad had formulated comprehensive theoretical framework of legal aspect of Islamic governance based on the fundamental principle and doctrine of the shariah, derived from the teaching of the Qur’an and the sunnah, while advocating democratic ideals and system based on conventional practice and requirement of modern context of nation state.